Hereditary periodic fever syndromes in adult rheumatology practice - O. V. Zhelyabina; M. S. Eliseev; M. N. Chikina (Современная ревматология)
Autoinflammatory diseases (AIDs) are a heterogeneous group of rare genetically determined, hereditary conditions characterized by unprovoked inflammatory episodes that are manifested by recurrent  fever and clinical symptoms reminiscent of rheumatic manifestations in the absence of autoimmune or infectious causes. The prevalence of hereditary AIDs in the population tends to increase. The list of AIDs is quite wide and includes various groups of diseases, including  those faced by not only a pediatrician, but also by an adult  rheumatology specialist. Practitioners do not know much about  hereditary AIDs, so the latter are often diagnosed late. However, due to the clinical introduction of new diagnostic techniques, primarily  genetic ones, and drug therapy in the detection and treatment of  these diseases, there has been clear progress, which makes it possible to change long-term prognosis in AIDs and to arouse increasing interest in the diseases not only among pediatricians, geneticists, but also among rheumatologists and general practitioners.